2017
DOI: 10.1159/000464103
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Up-Dosing of Subcutaneous Immunotherapy with a Registered Allergoid Birch Pollen Preparation

Abstract: Background: Early pollen flight and new allergens prolonging the pollen season means that the time for up-dosing of allergen-specific subcutaneous immunotherapy (SCIT) outside the pollen season becomes shorter. Hence, for patients who wish or need to be up-dosed faster, an accelerated induction regimen would provide a useful treatment option. Methods: An accelerated up-dosing regimen (0.1-0.3-0.5 mL at weekly intervals) was compared to conventional up-dosing (0.05-0.1-0.2-0.3-0.4-0.5 mL at weekly intervals) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…They identified that doses ≥20,000 UA and 18,000 TU improve the threshold of symptoms in nasal provocation tests and increase blocking antibody levels, respectively [ 67 , 68 ]. This molecular result was also shown with allergoids of birch (Allergovit ® Birch phase-II study and PURETHAL ® phase-IV study) [ 69 , 70 ].…”
Section: Allergoidssupporting
confidence: 61%
“…They identified that doses ≥20,000 UA and 18,000 TU improve the threshold of symptoms in nasal provocation tests and increase blocking antibody levels, respectively [ 67 , 68 ]. This molecular result was also shown with allergoids of birch (Allergovit ® Birch phase-II study and PURETHAL ® phase-IV study) [ 69 , 70 ].…”
Section: Allergoidssupporting
confidence: 61%
“…It thus provides an explanation for the efficacy of recombinant and synthetic allergen derivatives in AIT. Our observation may also explain why denatured allergen extracts (ie, allergoids) which are currently used in clinical practice for AIT can induce IgG antibodies against the wild‐type allergens and thus provide a mechanism for the mode of activity of allergoids in AIT . Finally, promising results have been obtained in AIT studies with a new type of allergy vaccines which are based on carrier‐bound allergen‐derived peptides which induce mainly peptide‐specific IgG antibodies which also strongly inhibit polyclonal IgE binding of allergic patients toward conformational epitopes .…”
Section: Discussionmentioning
confidence: 77%
“…To increase the safety of AIT, denatured allergen extracts termed allergoids have been introduced in which the native allergens have been chemically modified to lose their structure and conformational IgE epitopes . Despite the loss of the native structure, allergoids seem to induce allergen‐specific blocking IgG antibodies which are thought to be responsible for clinical efficacy of AIT besides alterations of cellular and cytokine responses . With the availability of recombinant allergens and DNA as well as peptide‐based technologies, recombinant and synthetic allergen derivatives have been engineered for several important allergens which resemble many features of allergoids, in particular reduced IgE reactivity and reduced allergenic activity .…”
Section: Introductionmentioning
confidence: 99%
“…Rush schedules with allergoids have also proven safe in previous studies [7,8], and a recent controlled study by Chaker et al [9] showed that an abbreviated build-up schedule with a 6-grass pollen allergoid extract (4 injections) was as safe and well-tolerated as the conventional 7-injection updosing schedule [9]. The aim of this retrospective study was to investigate the safety of the abbreviated build-up phase of pollen allergoids in real life.…”
mentioning
confidence: 94%